Evaluación de la descomposición química y actividad hipoglucemia de extractos de hojas y corteza de anacardium occidentales L. (Marañón). - Ramón Japón, Geovanny Efrén (2015)
Diabetes in our country is the principal disease causing death according to the Ministry of Public Health. The search for new ways to combat and taking into account the increased use and the good results obtained with medicinal plants in research for treating this disease. This study aims to evaluate the chemical composition and pharmacological activity as hypoglycemic extracts of leaves and bark of Anacardium occidentale L. (cashew). This research was conducted at the Academic Unit of Chemical Sciences and Health at the Technical University of Machala. The leaves and bark of the plant were harvested. Quality control drug was performed, residual moisture and ash results showed within normal parameters. Extracts was obtained and the respective quality control (refractive index, density, pH, ° Brix and total solids) was analyzing. The difference was established in the chemical composition of the extracts. Phytochemical screening determined that leaf extract shows more metabolites that bark extract. Mass spectrometry differenced the presence of quercetin in leaves and quantification of flavonoids and phenols established that leaf extract contain highest concentrations of these metabolite. Finally, the hypoglycemic activity of the hydroalcoholic extracts was evaluated in Wistar rats with hyperglycemia induced by glucose 40%. The dose for administration of each extract was 750 mg / kg. A good result in leaf extract that behaved like drug metformin, preventing glucose levels reach the positive control was obtained for hyperglycemia. The bark extract hasn’t hypoglycemic activity but contained metabolites that may have other pharmacological property.